Pharmacogenetic research in partnership with American Indian and Alaska Native communities. (July 2014) - Woodahl, Erica L; Lesko, Lawrence J; Hopkins, Scarlett; Robinson, Renee F; Thummel, Kenneth E; Burke, Wylie
Pharmacogenetics is a subset of personalized medicine that applies knowledge about genetic variation in gene–drug pairs to help guide optimal dosing. There is a lack of data, however, about pharmacogenetic variation in underserved populations. One strategy for increasing participation of underserved populations in pharmacogenetic research is to include communities in the research process. We have established academic–community partnerships with American Indian and Alaska Native people living in Alaska and Montana to study pharmacogenetics. Key features of the partnership include community oversight of the project, research objectives that address community health priorities, and bidirectional learning that builds capacity in both the community and the research team. Engaging the community as coresearchers can help build trust to advance pharmacogenetic research objectives.